2010
DOI: 10.1128/jvi.00994-10
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Flux between the Endoplasmic Reticulum and Mitochondrion Contributes to Poliovirus-Induced Apoptosis

Abstract: We show that poliovirus (PV) infection induces an increase in cytosolic calcium (Ca2+) concentration in neuroblastoma IMR5 cells, at least partly through Ca2+ release from the endoplasmic reticulum lumen via the inositol 1,4,5-triphosphate receptor (IP3R) and ryanodine receptor (RyR) channels. This leads to Ca2+ accumulation in mitochondria through the mitochondrial Ca2+ uniporter and the voltage-dependent anion channel (VDAC). This increase in mitochondrial Ca2+ concentration in PV-infected cells leads to mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
62
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 32 publications
1
62
0
1
Order By: Relevance
“…The decrease in Herp levels followed the same dynamics as the previously described increase in cytosolic Ca 2+ concentration during PV infection associated with cell progression to apoptosis (Brisac et al, 2010). We found that Herp restricted the PV-induced increase in cytosolic Ca 2+ concentration.…”
Section: Herpsupporting
confidence: 66%
See 4 more Smart Citations
“…The decrease in Herp levels followed the same dynamics as the previously described increase in cytosolic Ca 2+ concentration during PV infection associated with cell progression to apoptosis (Brisac et al, 2010). We found that Herp restricted the PV-induced increase in cytosolic Ca 2+ concentration.…”
Section: Herpsupporting
confidence: 66%
“…These values were also normalized against those for mock-infected cells (n-fold increase/mock). chromatin condensation and fragmentation by flow cytometry, as previously described (Brisac et al, 2010;Estaquier et al, 1994). As expected, the time course of PV-induced apoptosis (Fig.…”
mentioning
confidence: 72%
See 3 more Smart Citations